Celiac Plexus Block with versus without Botulinum Toxin Type A for Pancreatic Cancer Pain: A Retrospective Comparative Study - Kaehong Lee; Seungpyo Nam; Seungcheol Yu; Jeongsoo Kim (Pain Medicine, 2026)
Abstract Objective To evaluate whether the addition of botulinum toxin type A (BTX) to celiac plexus block (CPB) is associated with improved analgesic outcomes in patients with pancreatic cancer pain. Design Retrospective observational study. Setting Single-center tertiary hospital. Subjects A total of 60 patients with pancreatic cancer pain who underwent fluoroscopy-guided CPB between January 2022 and November 2025. Methods Patients were divided into CPB only (n = 34) and CPB with BTX (n = 26) groups. Pain intensity (numerical rating scale, NRS), opioid consumption (morphine milligram equivalents, MME), and need for rescue interventions were assessed at 4, 8, and 12 weeks. The primary outcome was the proportion of positive responders at 4 weeks, defined as ≥ 2-point reduction in NRS from baseline, no increase in opioid use, and no additional interventions. Results The proportion of positive responders at 4 weeks was significantly higher in the CPB + BTX group compared to the CPB only group (65.4% vs. 8.8%, p < 0.001), with sustained differences at 8 and 12 weeks. The CPB + BTX group showed significantly lower pain scores at all follow-up time points and required fewer rescue interventions, including no cases of neurolysis. Kaplan–Meier analysis demonstrated a longer duration of analgesic response in the CPB + BTX group (p < 0.001). In multivariable analysis, BTX use was independently associated with treatment success (OR = 20.75, p < 0.001), while distant metastasis was a negative predictor. No serious adverse events were observed. Conclusions CPB with BTX was associated with improved analgesic outcomes for pancreatic cancer pain compared to CPB only. The addition of BTX resulted in higher responder rates, sustained pain reduction, and reduced need for rescue interventions. BTX may represent a non-destructive adjunct to CPB and warrants further prospective validation.